Considering rhythms of emotional proximity: an alternative approach to directing theatre in a violent society - Herbst, Rone (Department of Drama, 2016)
This inquiry is concerned with realistic representations of violence on stage within a South African context. Inside this broad frame I focus on why this directorial approach is a problem and I propose a possible solution in a directorial intervention with mise-en-scène, which attempts to regulate the audience's emotional immersion and distance through theatre apparatus. This notion is supported both by Psychological research into the problem of violence in South Africa, and by Theatre and Performance studies, with author Lilie Chouliaraki (2013) arguing for the "in-between" of theatre as a means to approaching violence. Conceptually, I propose working with theatre apparatus in a spatial triad, which is located within Peter Brook's ideas around an "empty space", the post-Brechtian according to David Bennett, which is concerned with both distance and emotional immersion, and the spatial trialectics of Henri Lefebvre and Edward Soja, who argue for the insertion of a "thirdspace" in order to counter the limited workings of binaries. This conceptual frame translates into praxis in the form of theatre apparatus such as interruption and disruption of the narrative, working with metaphor and gesture, "playing" with time, duration and repetition and working towards moments of extreme intensity before a pause is inserted into the action. I propose these apparatus as the findings of a series of Practice as Research projects which formed part of this study, and as the tools for my final Thesis Production. This project will take place in November, 2015 in the form of an adaptation of a novel, where my objective will be to create a rhythm of emotional audience involvement. My aim is to test whether the apparatus I have discovered in this study are able to regulate the emotional proximity of the audience to the violence on stage, hopefully providing an alternative approach to working with violence in an already violent society.